Metabolismo de flúor e cálcio de indivíduos residentes em uma área de fluorose endêmica no estado da paraíba antes e após a implantação de um sistema de desfluoretação - Souza, Consuelo Fernanda Macedo de (2011)
The aim of this study was to evaluate fluoride and calcium metabolism in a region endemic on fluorosis (Brejo das Freiras-PB) after the implantation of a defluoridation system. There were 13 children and 16 adults as volunteers of this study. In order to evaluate ingestion it was used the methodology of the duplicated dish. To analyze fluoride derived from dentifrice the volunteer were asked to simulate the way they brush their teeth and the descart was collected. For the analysis of excretion it was used the 24 hours urine collection. All the samples collected was evaluated for fluoride concentration, through the fluoride specific electrode and through HMDS technique. The calcium was analyzed through arsenazo II methodology. The metabolism evaluation occurred at three periods named D1 (baseline, that is, before the defluoridation system was implanted), D2 (after a period of thirty days of the implantation of the system) and D3 (after after a period of six months of the implantation of the system). All data analysis was done through statistical packages (SPSS and graphpad). It could be observed that ingestion and excretion of fluoride diminished after the implantation of the system moreover fluoride retention decreased. Fluorosis risks decreased from twelve children to zero six months after the defluoridation system was implanted. We concluded that the defluoridation system was effective for diminishing fluoride retention as well as the fluorosis risk.